Religion, morality and the law - Pennock, James Roland; Chapman, John W. (Nomos, 1988)
Introduction / J. Roland Pennock -- Jean Bodin : the paradox of sovereignty and the privatization of religion / Stephen Holmes -- Liberalism, neutralism, and rights / Eric Mack -- Comment on Holmes, "Jean Bodin : the paradox of sovereignty and the privatization of religion" / John H. Mansfield -- Bayle's commonwealth of atheists revisited / George A. Kelly -- A Christian critique of Christian America / Stanley Hauerwas -- Comment on "A Christian critique of Christian America" / David G. Smith -- The wall of separation and legislative purpose / Louis Henkin -- Religion, public morality, and constitutional law / David A.J. Richards -- Divine sanction and legal authority : religion and the infrastructure of the law / Lisa Newton -- Bringing the messiah through the law : a case study / Robert M. Cover -- Natural law and creation stories / Ronald R. Garet -- Politics and religion in America : the enigma of pluralism / John Ladd